Intonation in African Tone Languages - (:unkn) unknown (My University, 2016)
The volume brings together two-underinvestigated areas of intonation typology. While tone languages make up to 70 percent of the world's languages, only few have been explored for intonation. And even though one third of the world's languages are spoken in Africa, and most sub-Saharan languages are tone languages, recent collections on tone and intonation typology have almost entirely ignored African languages. This book aims to fill this gap.
Keywords: African Research